Genome Mining Uncovers NRPS and PKS Clusters in Rothia dentocariosa with Inhibitory Activity against Neisseria Species - Elvis Achondou Akomoneh; Zina Gestels; Saïd Abdellati; Katleen Vereecken; Koen Bartholomeeusen; Dorien Van den Bossche; Chris Kenyon; Sheeba Santhini Manoharan-Basil (MDPI AG, 2023)
The growing global threat of antimicrobial resistance is reaching a crisis point as common bacterial infections, including those caused by pathogenic Neisseria species, are becoming increasingly untreatable. This is compelling the scientific community to search for new antimicrobial agents, taking advantage of computational mining and using whole genome sequences to discover natural products from the human microbiome with antibiotic effects. In this study, we investigated the crude extract from a Rothia dentocariosa strain with demonstrated antimicrobial activity against pathogenic Neisseria spp. by spot-on-lawn assay. The genomic DNA of the R. dentocariosa strain was sequenced, and bioinformatic evaluation was performed using antiSMASH and PRISM to search for biosynthetic gene clusters (BGCs). The crude extract with potential antimicrobial activity was run on Tricine-SDS-PAGE, and the putative peptides were characterised using liquid chromatography-tandem mass spectrometry (LC-MS). The crude extract inhibited the growth of the pathogenic Neisseria spp. Six BGCs were identified corresponding to non-ribosomal peptide synthases (NRPSs), polyketide synthases (PKSs), and ribosomally synthesised and post-translationally modified peptides. Three peptides were also identified corresponding to Actinorhodin polyketide putative beta-ketoacyl synthase 1. These findings serve as a useful reference to facilitate the research and development of NRPS and PKS as antimicrobial products against multidrug-resistant N. gonorrhoeae.